Transformational Leadership in School-Based Management (SBM) - Anwar, Saiful (Proceeding International Conference on Education, 2025)
This study aims to examine the strategies of madrasah principals in strengthening ideal influence, inspirational motivation, intellectual stimulation, and individual attention towards teachers and education staff in the implementation of Transformational Leadership in School-Based Management (SBM) at MTsN 7 Tulungagung. The approach used is post-positivistic with data collection techniques through participant observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data condensation, data presentation, and concluding, with validity tested through triangulation, extended attendance, and discussions with colleagues. The results of the study indicate that madrasah principals integrate the vision and mission of the madrasah into the work program, provide motivation through moral support and rewards, improve teacher competency through training, provide adequate learning facilities, and meet the needs of individual educators. Overall, madrasah principals play a central role in implementing Transformational Leadership with a collaborative, inspirational, and value-based approach. This strategy creates an educational environment that supports the development of educators' potential and encourages the creation of quality learning that is in line with the madrasah's vision as a center for the development of faith, science, and technology.